Peningkatan Literasi Investasi Siswa SMAN 1 Kutasari - Ossi Ferli; Taufiq Hidayat; Ajeng Rida Riyanti; Catur Nugrahani; Yola Pangestu Anggraeni (I-Com: Indonesian Community Journal, 2024)
Generation Z dominates the population in Indonesia at present. According to data, the investors currently dominating the capital market in Indonesia are the young generation. In fact, knowledge about finance and investment is still uneven among the young generation. This community service aims to investigate the level of financial knowledge and literacy of Generation Z in the context of investment and identify their interest in future investment activities. The research methodology involves the use of questionnaires distributed to a sample of Generation Z, with the collection of primary data as the basis for analysis. The results indicate that, overall, the financial knowledge of Generation Z regarding investment and financial literacy is still lacking, with the majority of respondents showing limited understanding. Nevertheless, the findings also reveal a sufficiently high interest from Generation Z to engage in investments in the future. These findings indicate the potential to enhance financial literacy among Generation Z while leveraging their interest in developing skills and financial understanding to achieve better investment goals in the future.